Heavy isotope labeling and mass spectrometry reveal unexpected remodeling of bacterial cell wall expansion in response to drugs - Atze, Heiner; Liang, Yucheng; Hugonnet, Jean-Emmanuel; Gutierrez, Arnaud; Rusconi, Filippo; Arthur, Michel (eLife, 2022)
Antibiotics of the β-lactam (penicillin) family inactivate target enzymes called D,D-transpeptidases or penicillin-binding proteins (PBPs) that catalyze the last cross-linking step of peptidoglycan synthesis. The resulting net-like macromolecule is the essential component of bacterial cell walls that sustains the osmotic pressure of the cytoplasm. In Escherichia coli, bypass of PBPs by the YcbB L,D-transpeptidase leads to resistance to these drugs. We developed a new method based on heavy isotope labeling and mass spectrometry to elucidate PBP- and YcbB-mediated peptidoglycan polymerization. PBPs and YcbB similarly participated in single-strand insertion of glycan chains into the expanding bacterial side wall. This absence of any transpeptidase-specific signature suggests that the peptidoglycan expansion mode is determined by other components of polymerization complexes. YcbB did mediate β-lactam resistance by insertion of multiple strands that were exclusively cross-linked to existing tripeptide-containing acceptors. We propose that this undocumented mode of polymerization depends upon accumulation of linear glycan chains due to PBP inactivation, formation of tripeptides due to cleavage of existing cross-links by a β-lactam-insensitive endopeptidase, and concerted cross-linking by YcbB.
Keywords: peptidoglycan; cell wall; antibiotics; mass spectrometry; peptidoglycan polymerization; L; D-transpeptidase